Experimental study on fire risk of buildings' U-shaped exterior wall on flame propagation of insulation material on plain and plateau. (September 2015) - Yan, Weigang; Shen, Yang; An, Weiguang; Jiang, Lin; Sun, Jinhua
This study provides an understanding of the fire risk of building's exterior wall geometry design at different altitudes. The influences of the U-shaped exterior wall geometry on upward flame spread over insulation material on plain and plateau were studied through laboratory-scale experiments. A hypothesis of pseudo chimney effect is provided. Results show that in both plain and plateau, the flame spread rate and the mass loss rate increase as the U-shaped geometry becomes deeper. The time for flame to propagate a certain distance follows an exponential decreasing trend, while it could be concluded that the upper and lower boundaries indicate the time for that of flat and enclosure geometry, respectively. Moreover, the flame spread rate is much higher in plain than in plateau. The key parameter is the upward flow induced by the air entrainment from bottom and front sides of the geometry which enhances the heat feedback.